PENGARUH KARAKTERISTIK TUJUAN ANGGARAN TRHADAP KINERJA APARAT PEMERINTAH DAERAH (STUDI EMPIRIS PADA SKPD KABUPATEN KAMPAR) - Della Adriadiva; Raja Adri Satriawan; Rheny Afriana Hanif (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
Local government management of accountability , not separated from the local government budget. In the planning of budget there are some characteristic purpose of the budget that is budgetary participation, budget clarity, budget feedback, budget evaluation, and budget goal difficulties. The existence of the budget’s purpose will clearly facilitate individuals to draw up the target budget.The purpose of this study was to re-examine the effect of budgetary goal characteristics to the performaance of local government. This study performed on local government in SKPD Kampar Regency with the second, third, and fourth echelon position. The object of this study is SKPD Kampar regency. Primary data collection method conducted with survey technique by providing questions to respondents by the questionnaire and the total of questionnaire is 108.The result of this study showed that budgetary goal characteristics (budgetary participation, budget clarity, budget feedback, budget evaluation) had a positive and signifikan effect in performance of local government. While difficulties in the budget’s purpose doesn’t had significant effects on the performance of local government of Kampar Regency.Keywords: Budgetary, Performance of Local Government.